Sufism Studies from a Gender Perspective: The Role and Experience of Rabiah Al-Adawiyah in the Sufi Tradition - Qibtiyah, Luthfatul; Hasanah, Uswatun; Hidayati, Nurul (Proceedings of International Conference on Muslim Society and Thought, 2024)
Abstract: This study explores the role and experiences of Rabiah al-Adawiyah in the Sufi tradition with a focus on gender perspectives. Rabiah, as one of the central figures in the history of Sufism, is known for her significant contribution to the development of Sufism teachings, especially in the concept of divine love (mahabbah) and spiritual asceticism. This study uses a qualitative approach with a type of literature study to explore the poetry of a prominent Sufi woman, Rabiah al-Adawiyah, to understand how they responded to and shaped their views on spirituality in a context that is often dominated by male narratives. The research findings demonstrate that Rabiah not only enriched Sufi theology with a feminine perspective but also challenged gender stereotypes in Islamic spirituality. Rabiah al-Adawiyah emerges not only as an inspirational Sufi figure but also as a crucial symbol of women’s spiritual potential within the Sufi tradition. Her contributions have left a profound spiritual legacy and continue to inspire contemporary discussions on equality and inclusivity in Islamic religious practice.